2u+38=7(u-1)

Simple and best practice solution for 2u+38=7(u-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2u+38=7(u-1) equation:


Simplifying
2u + 38 = 7(u + -1)

Reorder the terms:
38 + 2u = 7(u + -1)

Reorder the terms:
38 + 2u = 7(-1 + u)
38 + 2u = (-1 * 7 + u * 7)
38 + 2u = (-7 + 7u)

Solving
38 + 2u = -7 + 7u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-7u' to each side of the equation.
38 + 2u + -7u = -7 + 7u + -7u

Combine like terms: 2u + -7u = -5u
38 + -5u = -7 + 7u + -7u

Combine like terms: 7u + -7u = 0
38 + -5u = -7 + 0
38 + -5u = -7

Add '-38' to each side of the equation.
38 + -38 + -5u = -7 + -38

Combine like terms: 38 + -38 = 0
0 + -5u = -7 + -38
-5u = -7 + -38

Combine like terms: -7 + -38 = -45
-5u = -45

Divide each side by '-5'.
u = 9

Simplifying
u = 9

See similar equations:

| r-10/3=3 | | .42/7.00=x/100 | | (2x-1)(2x+7)=0 | | 3(p-13)+4=13 | | x^5-ax^2-ax+1=0 | | -6(8v-4)=6(6v+4) | | n+9=4v-6 | | 8y=3x-12 | | 2(1+8x)=4(4x+8) | | ax+y=bx+K | | -6(4x-6)=-18-6x | | (3i+8)(6i-7)= | | 4(x+5)-2x+2=3(2x-4)+x+9 | | x+90+70=180 | | -3(4v+8)=-18-6v | | H(t)=-16t^2+342+1000 | | 4/2x-2916=1/9 | | x^2+6x+12=2x-1 | | 30=-w+247 | | -7b+28=-8(5+3b) | | 4(32-2b)=144 | | 242-u=133 | | 1+7x=4x+16 | | 3(2x+5)=(3x+3) | | 5m+m-2m=20 | | 12n=7 | | 7p+2p+2p-p-2p=16 | | 16b-9b-b=18 | | y=-5t^2+20t+60 | | √2/2x-54=1/3 | | ln0.9/ln2= | | 17c+2c+2c-12c=9 |

Equations solver categories